Percutaneous left atrial appendage closure in the presence of thrombus: A feasibility report. (31st October 2019) - Bordignon, Stefano; Bologna, Fabrizio; Chen, Shaoje; Konstantinou, Athanasios; Tsianakas, Nikolaos; Tohoku, Shota; Trolese, Luca; Chun, KR Julian; Schmidt, Boris
Abstract: Background: Patients with a left atrial appendage thrombus (LAAT) despite oral anticoagulation (OAC) are at high risk of thromboembolism (TE) and a relevant proportion of LAAT do not resolve under continued OAC. Left atrial appendage closure (LAAC) in the presence of LAAT was anecdotally described as a therapeutic option to prevent TE in the patients. Objective: To describe the feasibility of LAAC despite LAAT in consecutive patients. Methods: We searched the LAAC database of our center to identify patients in whom a LAAC was performed despite evidence of a thrombus in the LAA. All procedures were performed under transesophageal echocardiography guidance, no angiographies were performed to avoid LAAT dislocation. An Amulet Occluder device was preferred to allow proximal implantation and sealing of the LAA. Results: Nine patients were identified. The mean age was 68.1 ± 10.7 years, four were female, mean CHADSVASC and HASBLED were 3.6 ± 1.7 and 3.0 ± 1.0. Eight of nine patients were on OAC, one patient was under lone aspirin therapy because of bleeding. The mean distance between the LAAT and the estimated landing zone was 18 ± 6 mm, the minimal distance was 11 mm. The mean landing zone was 21 ± 3 mm, devices with a mean size of 25 ± 4 mm were chosen for implantation. All implantation succeeded, only two patients required an intraprocedural replacement. No procedural complication nor short term thromboembolic complication during a follow up of 138 ± 149 days were recorded. Conclusion: In the presented series a percutaneous LAAC despite a LAAT resulted to be feasible and safe.